Class-wide behaviour management practices reported by pre-and elementary school teachers: Relations with individual and contextual characteristics - Nadeau, Marie-France; Massé, Line; Lagacé-Leblanc, Jeanne; Verret, Claudia; Gaudreau, Nancy (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
This study examined the use of inclusive practices by 1,373 Quebec teachers to promote prosocial behaviour, according to their individual and contextual characteristics. Two questionnaires were used: a sociodemographic and a validated Classroom Behaviour Management Practices Inventory (N = 68 items; 2 dimensions/7 scales α = .70 to .90). Results from descriptive and univariate variance analysis showed that proactive /positive dimension practices (e.g., rules, instructional, reinforcement-based) are used more frequently than reductive dimension practices (e.g., educational consequences), although some of the latter are frequently used. Hierarchical models indicate significant interrelationships with teachers characteristics and the scales of classroom behaviour management practices, but for a small proportion of explained variance.